1998
DOI: 10.1002/(sici)1521-3757(19980116)110:1/2<117::aid-ange117>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

RNA‐Aminoglycosid‐Wechselwirkungen: Design und Synthese von „Amino‐aminoglycosiden”︁ und deren Bindung an RNA

Abstract: Die elektrostatische Wechselwirkung ist entscheidend bei der Bindung von Aminoglycosid‐Antibiotica an RNA. Dies ergab der Austausch von OH‐ gegen NH2‐Gruppen, z.B. in Kanamycin A 1. Das Derivat 2 inhibiert ein Hammerhead‐Ribozym viel stärker als 1. Es wird vorgeschlagen, daß die räumliche Anordnung der positiven Ladungen die Bindungsstärke der Aminoglycoside bestimmt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Experimental studies on hammerhead RNA ± drug complexes containing designed aminoglycoside derivatives in which the number, the basicity, or the flexibility of the attachment of ammonium groups has been systematically altered [30,128,192] support the model of structural electrostatic complementarity. [34] When either the number or the charge density of ammonium groups in aminoglycosides is increased, the inhibitory activity of the compounds is enhanced.…”
Section: Electrostatic Forces and Metal Ion Bindingmentioning
confidence: 87%
See 2 more Smart Citations
“…Experimental studies on hammerhead RNA ± drug complexes containing designed aminoglycoside derivatives in which the number, the basicity, or the flexibility of the attachment of ammonium groups has been systematically altered [30,128,192] support the model of structural electrostatic complementarity. [34] When either the number or the charge density of ammonium groups in aminoglycosides is increased, the inhibitory activity of the compounds is enhanced.…”
Section: Electrostatic Forces and Metal Ion Bindingmentioning
confidence: 87%
“…They can govern, however, specific recognition in the binding of conformationally constrained polycationic molecules to RNA folds as revealed by investigations on the interaction of aminoglycosides with different RNA targets. [30,34,128,129,192] In a quantitative approach using surface plasmon resonance, it has been demonstrated that increasing the ionic competition by adding salt to RNA ± aminoglycoside complexes decreased both the specific and nonspecific drug binding to about the same extent. [128] In other words, the electrostatic component of the binding energy contributed, as expected, to the unspecific binding but also, to a remarkable extent, to the specific binding.…”
Section: Electrostatic Forces and Metal Ion Bindingmentioning
confidence: 93%
See 1 more Smart Citation
“…[23] We have demonstrated that substituting a hydroxyl with an amino group can convert a very poor RNA binder, such as kanamycin A, to a reasonably strong one. Thus, 6''-amino-6''-deoxykanamycin A is as effective as kanamycin B, a natural product containing five amino groups.…”
Section: Discussionmentioning
confidence: 99%
“…Tobramycin binds a number of natural RNAs with higher affinity than kanamycin B (Figure 1), [12,18,23] although both compounds contain five amino groups. The only difference between the two antibiotics is an additional hydroxyl group at the 3'-position in kanamycin B.…”
Section: Discussionmentioning
confidence: 99%